Penerapan Metode Jigsaw dan Canva dalam Pembelajaran Fikih untuk Meningkatkan Hasil Belajar Siswa MI - Leli Amaliyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2023)
The low learning outcomes of students encourage teachers to try to improve the learning process in the classroom. This study aims to improve student learning outcomes by implementing the Jigsaw method assisted by Canva in fiqh learning in class VI A MI PUI Cicalung. This type of research is classroom action research (CAR), which is carried out in two cycles, with each cycle consisting of four stages, namely planning, implementation, observation, and reflection. The data collection methods used in this study are observation, testing, and documentation. The data obtained were analyzed using descriptive statistical techniques, which were then presented in narrative and graphic form. The results of the study showed that the application of the Jigsaw method assisted by Canva can improve student learning outcomes in class VI A MI PUI Cicalung. This can be seen from the increase in the percentage of student learning outcomes in cycle I, which increased from 58% to 88%, which shows an increase of 30% compared to the pre-cycle conditions. In cycle II, student learning outcomes experienced another significant increase, namely from 88% to 100%, which means there was an increase of 12% compared to cycle I.